POPULAR KNOWLEDGE AND CONDUCTS AGAINST DOMESTIC ELETRIC ACCIDENTS IN IMPERATRIZ CITY - Oliveira, Alexsander Silva de (2021)
Objective: To discuss knowledge and pracitces of people against eletctroshock accidents in home. Methods: Cross-sectional, descritive and quantitative study, using a quiz, with 17 questions, collected in 2019, in Imperatriz. Results: Sample of 390 people. Age ranged from 18 to 78. In electroshocks, 50,8% was electrical outlets, 39,1% in home appliances. In prevention, 83% don't use plug protectors, 50,5% handle wet electricity, 82,8% barefoot, 10% uses rubber gloves. Acting 369 wouldn't keep calm, 168 would push the victim with their hands, 256 turns off the power supply, 310 pushes the victim with broomstick. In aid measures, 37,5% don't know emergency number. Furthermore, 62,6% don't know how to identify cardiopulmonary arrest, and 64,9% don't know how to do cardiopulmonary resuscitation. Concerning interest, 79,7% would like to learn to recognize such grievance, and 11% to know the number of Emergency Service. Conclusion: It's evident that there is a disability for identification and resolution of a grievance. Finally, there is an interest in to get knowledge that optimizes the intervention.